ANALYSIS OF BANK HEALTH LEVEL USING RISK PROFILE, CORPORATE GOVERNANCE, EARNINGS AND CAPITAL EVALUATION METHODS AT PT BANK ACEH SYARIAH IN FOR THE 2017-2023 PERIOD - Rahayu, Rahayu; Muhayatsyah, Ali; Yoesoef, Yoesrizal Muhammad (J-ISCAN: Journal of Islamic Accounting Research, 2024)
This study aims to analyze the health level of a bank using the RGEC method (risk profile, good corporate governance, earnings, capital). The data used in this research is secondary data in the form of financial reports and governance reports of PT. Bank Aceh for the years 2017-2023. The results of the study indicate that the health level of Bank Aceh using the risk profile with the non-performing financing ratio and financing to deposit ratio shows that Bank Aceh achieved an excellent rating. Furthermore, the health level of Bank Aceh using good corporate governance indicates that Bank Aceh falls into the good category. The health level of Bank Aceh using earnings with the return on asset ratio shows that Bank Aceh is in the very good category, and the health level of Bank Aceh using capital with the capital adequacy ratio shows that Bank Aceh is in the very good category. Overall, from 2017-2023, Bank Aceh was ranked composite one with a very healthy predicate and composite total scores of 86% and 100%, respectively.